FAKTOR-FAKTOR YANG MENDORONG PRAKTIK NIKAH SIRI DALAM KONTEKS SOSIAL MODERN - Mochammad Agus Rachmatulloh; Adella Devi Febianti; Mufidatul Khoiriyah; Dian Nur Hidayati; Shinta Rohmatul Fitroh; Rahma Fitria Fatma Sari; Moh. Hamdan Mannan Mukafi; Muhammad Arif Dwi Sahputra (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
In the modern social context, the practice of unregistered marriage is becoming increasingly prominent as a phenomenon with complex nuances. This is due to a number of external and internal factors which also encourage and influence people to do so. A deep understanding of the factors that drive this phenomenon is very important to develop appropriate strategies to overcome and reduce negative impacts in modern society. This is normative legal research using a conceptual approach. The factors behind the occurrence of unregistered marriages are economic factors, not being old enough, official/work or school ties, the assumption that unregistered marriages are legal according to religion and registration is only an administrative order, pregnancy out of wedlock as an effect of promiscuity, and social. The impacts that cause unregistered marriages in the modern social era are positive impacts, namely avoiding adultery, while negative impacts include legal, economic, sociological, educational, cultural and psychological impacts. The conditions for a valid marriage according to applicable law in Indonesia are that it be carried out according to the laws of each religion and belief, and recorded according to applicable laws and regulations.